2002
DOI: 10.1021/jf020690l
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Anthocyanins from Blueberries and Serum Antioxidant Status in Human Subjects

Abstract: In recent years, numerous studies have shown that the polyphenolics present in fruit and vegetable products exhibit a wide range of biological effects. However, there is little reliable information on the absorption of glycosylated and acylated anthocyanins in humans. In the present study, the absorption of anthocyanins in humans was investigated after the consumption of a high-fat meal with a freeze-dried blueberry powder containing 25 individual anthocyanins including 6 acylated structures. Nineteen of the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
278
1
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(301 citation statements)
references
References 35 publications
6
278
1
6
Order By: Relevance
“…When flavanone aglycones (FA) consisting abundantly of eriodictyol were ingested in humans, the difference in absorption characteristics after ingestion of FG or FA was also examined. Flavonoid metabolites in plasma were reported to be detected at an early hour after ingestion of flavonoids in humans (15)(16)(17)(18)(19). We examined the metabolites in plasma up to 4.0 h after ingestion of FG with water and FA with water in humans in this study.…”
mentioning
confidence: 99%
“…When flavanone aglycones (FA) consisting abundantly of eriodictyol were ingested in humans, the difference in absorption characteristics after ingestion of FG or FA was also examined. Flavonoid metabolites in plasma were reported to be detected at an early hour after ingestion of flavonoids in humans (15)(16)(17)(18)(19). We examined the metabolites in plasma up to 4.0 h after ingestion of FG with water and FA with water in humans in this study.…”
mentioning
confidence: 99%
“…Depending on nutritional custom, the daily intake of these compounds in humans is estimated to be a few hundred milligrams per day [Hollman and Katan, 1999]. They are absorbed by stomach [Passamonti et al, 2003] and intestinal cells [Talavera et al, 2004] and are rapidly detected in plasma in vivo [Mazza et al, 2002] suggesting that they are bioavailable to exert their biological effects. Consumption of anthocyanins has been shown to reduce the risk of coronary heart disease [Dell'Agli et al, 2004] and cancer [Hou, 2003].…”
mentioning
confidence: 99%
“…In addition, these compounds also correlate with better performance of the enzymes of the endogenous antioxidant system 24 . Bioavailability studies found that anthocyanins and their metabolites are largely present in the liver, being associated with high hepatic antioxidant capacity 25 . Thus, the addition of 2% freeze-dried jaboticaba peel to the high-fat diet might have protected the liver from obesity-induced oxidative stress by providing exogenous and endogenous antioxidants, preventing lipid oxidation 24 .…”
Section: Discussionmentioning
confidence: 99%